A rapid inversion technique for the measurement of longitudinal relaxation times of brain metabolites: application to lactate in high‐grade gliomas at 3 T. (25th July 2016) - Landheer, Karl; Sahgal, Arjun; Myrehaug, Sten; Chen, Albert P.; Cunningham, Charles H.; Graham, Simon J.
Abstract : The aim of this study was to develop a time‐efficient inversion technique to measure the T 1 relaxation time of the methyl group of lactate (Lac) in the presence of contaminating lipids and to measure T 1 at 3 T in a cohort of primary high‐grade gliomas. Three numerically optimized inversion times (TIs) were chosen to minimize the expected error in T 1 estimates for a given input total scan duration (set to be 30 min). A two‐cycle spectral editing scheme was used to suppress contaminating lipids. The T 1 values were then estimated from least‐squares fitting of signal measurements versus TI. Lac T 1 was estimated as 2000 ± 280 ms. After correcting for T 1 (and T 2 from literature values), the mean absolute Lac concentration was estimated as 4.3 ± 2.6 mm . The technique developed agrees with the results obtained by standard inversion recovery and can be used to provide rapid T 1 estimates of other spectral components as required. Lac T 1 exhibits similar variations to other major metabolites observable by MRS in high‐grade gliomas. The T 1 estimate provided here will be useful for future MRS studies wishing to report relaxation‐corrected estimates of Lac concentration as an objective tumor biomarker. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : A rapid inversion technique was combined with a lactate‐editing sequence to measure the lipid‐free longitudinal relaxation time of lactate, estimated to be 2000 ± 280 ms. Numerically optimized inversion times were used to maximize the precision for a set scan duration. The mean absolute concentration of lactate corrected for T 1 and T 2 was estimated as 4.3 ± 2.6 mm .